10.1002/9781118797914 (CrossRef Listing of Deleted DOIs, 2000)
This technical note describes and standardizes patient positioning and operating room setup for ankle arthroscopy in supine, prone, and lateral decubitus positions. The proposed configuration emphasizes ergonomic optimization, efficient cable management, and improved workflow for both surgeon and assistant. A reproducible organization of the arthroscopy tower and instrument table facilitates visualization, instrument handling, and safety while minimizing sterility breaches and technical incidents. This standardized setup enhances the efficiency, reproducibility, and overall safety of ankle arthroscopy, provided that sufficient space is maintained around the operating table.